2023
DOI: 10.31234/osf.io/3zbe2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The cognitive load effect in working memory: Refreshing the empirical landscape, removing outdated explanations

Abstract: Maintaining information in working memory often competes with concurrent processing of other information. This is reflected in the cognitive load effect, referring to the observation that processing tasks with a higher cognitive load result in lower memory performance. The cognitive load effect has been shown on many occasions in complex span tasks, which combine maintenance of memory items with a processing demand interleaved in between the presentation of the memory items. Two models of working memory, the T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…However, the concurrent tasks used in our experiments were similar to those implemented in previous studies in which they had affected the memory performance of children of the same age (Barrouillet et al, 2009; Camos & Barrouillet, 2011; Oftinger & Camos, 2018). Nevertheless, it may be noted that Langerock et al (2020) showed that, in adults, the manipulation of concurrent attentional demand (i.e., the cognitive load effect) has a weaker effect (or even none) in Brown-Peterson tasks than in complex span tasks used in the previously mentioned studies. Thus, one might expect that a stronger manipulation of cognitive load would be required to observe its effect in a Brown-Peterson task, especially in children.…”
Section: Discussionmentioning
confidence: 87%
“…However, the concurrent tasks used in our experiments were similar to those implemented in previous studies in which they had affected the memory performance of children of the same age (Barrouillet et al, 2009; Camos & Barrouillet, 2011; Oftinger & Camos, 2018). Nevertheless, it may be noted that Langerock et al (2020) showed that, in adults, the manipulation of concurrent attentional demand (i.e., the cognitive load effect) has a weaker effect (or even none) in Brown-Peterson tasks than in complex span tasks used in the previously mentioned studies. Thus, one might expect that a stronger manipulation of cognitive load would be required to observe its effect in a Brown-Peterson task, especially in children.…”
Section: Discussionmentioning
confidence: 87%